First trimester maternal plasma proteomic changes predictive of spontaneous moderate/late preterm delivery - Mavreli, Danai; Theodora, Mariana; Lambrou, George; Avgeris, Margaritis; Papantoniou, Nikolas; Traeger-Synodinos, Jan; Daskalakis, George; Kolialexi, Aggeliki (The Journal of Maternal-Fetal & Neonatal Medicine, 2023)
Identification of differentially expressed proteins (DEPs) in first trimester maternal plasma between pregnant women with a subsequent spontaneous moderate/late Preterm Delivery (sPTD) and women who delivered at term. The sPTD group consisted of women who delivered between 32°/7 and 366/7?weeks of gestation. Isobaric tags for relative and absolute quantification (iTRAQ) coupled with LC?MS/MS was used for the analysis of five first trimester maternal plasma samples obtained from women with a subsequent moderate/late preterm sPTD and five women with term deliveries. Enzyme-linked immunosorbent assay (ELISA) was further applied in an independent cohort of 29 sPTD cases and 29 controls to verify the expression levels of selected proteins. 236 DEPs, mainly linked to coagulation and complement cascade, were identified in first trimester maternal plasma obtained from the sPTD group. Decreased levels of selected proteins, namely, VCAM-1, SAA, and Talin-1, were further confirmed using ELISA, highlighting their potential as candidate predictive biomarkers for sPTD at32°/7 and 366/7?weeks of gestation. First trimester maternal plasma proteomic analysis revealed protein changes associated with subsequent moderate/late preterm sPTD.